An investigation into the contribution of NGOs to food security in Zimbabwe: a focus on CARE International Zimbabwe’s projects in ward 18 of Zaka district from 2000 up to 2014 - Gobvu, Ernias (Midlands State University, 2017)
Food security occupies a significant place in development discourse, planning and implementation. This study focused on examining the effectiveness of NGOs food security interventions, with particular focus on CARE International Zimbabwe’s projects in ward 18 of Zaka District. The primary objectives of the study was to establish the extent of food insecurity in ward 18 of Zaka District, and identifying food security interventions under CARE International Zimbabwe as well as identifying the challenges associated or faced by the organization in its efforts to ensure food security. A sample of 40 people from ward 18 community was used to gather the research information. Interviews and questionnaires have been instrumental in gathering research data. The empirical results showed that combating food insecurity through CARE International interventions is rather difficult, especially considering the challenges associated with the organization. The study therefore recommends that the organization should embark on long term sustainable projects like irrigation schemes through availing funds for the communities to acquire irrigation facilities to improve the effectiveness of its interventions in ensuring food security. The study also recommends the government to establish synergies with the third sector so as to ensure that a conducive environment prevail for the third sector to undertake its operation to promote food security in the country.